Prevalence, Knowledge, Attitude and Practices of Hepatitis B Virus Infection among Undergraduate Students in a Private Universuty in Abuja, Nigeria - Funke, Ogunkoya Oluseun; Salihu, Muhammad Baba; Nabeelah, Muhammad Taaha (International Journal of Human and Health Sciences (IJHHS), 2026)
Despite the widespread awareness of Hepatitis B virus, there still arises significant knowledge gaps, risky behaviors and poor vaccination coverage among university students. This study aims to determine the prevalence of hepatitis B virus (HBV) infection among undergraduate and to assess their knowledge, attitudes, risk factors, awareness, and vaccination status, with the goal of providing evidence-based recommendations for HBV prevention and control. This descriptive, cross-sectional study was conducted among 250 undergraduate students of Baze university in Abuja, Nigeria, selected through simple random sampling, between February and July of 2025. Data were collected using a structured, pre-tested questionnaire covering socio-demographics, medical history, behavioral risk factors, knowledge, and awareness of HBV. In addition, participants were screened for hepatitis B surface antigen (HBsAg) using a rapid immunochromatographic test kit (Labacon), with confirmatory testing performed for positive results. Of the 250 students screened, only one (0.4%) tested positive for HBV. Awareness was high, with 96% of respondents reporting knowledge of HBV, and 80.4% identifying the virus as the causative agent. However, significant misconceptions persisted, particularly regarding modes of transmission; 10.8% believed HBV could spread through casual contact, and 14.8% cited contaminated food or water. While 72% were aware of the availability of an HBV vaccine, only 38% were fully vaccinated and 50.8% remained unvaccinated. Notably, 75.6% expressed willingness to undergo free screening, and 82% recognized that university students are at heightened risk. Despite high levels of awareness, knowledge gaps and low uptake of vaccination and testing persist among university students, underscoring the need for targeted educational interventions, on-campus vaccination drives, and routine screening programs to reduce HBV risk in this population. International Journal of Human and Health Sciences Vol. 10 No. 01 Jan’26 Page: 29-38